ication of Management Function in Training at the Sanggar Dapur Seni Probo Wengker in Ponorogo Regency - Ones, Debriena; Hidajad, Arif (Solah, 2025)
This study aims to describe training management at Sanggar Dapur Seni Probo Wengker Ponorogo. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that training management at this studio encompasses four main functions: planning, organizing, directing, and controlling. During the planning phase, the studio develops a training schedule for instructional materials and divides classes based on students’ age levels and abilities. In the organizing stage, the studio establishes an organizational structure, arranges facilities, develops training materials, and assigns tasks to trainers according to their respective classes. The motivating stage includes motivating participants, coordinating between trainers and participants, and encouraging enthusiasm among students to participate in the training. Meanwhile, monitoring is conducted through administrative and financial evaluations, training implementation evaluations, and evaluations of facilities and infrastructure. Training evaluations are conducted periodically, including through UKKM (Competency Achievement Assessment) activities. These findings indicate that the management of dance training at the Dapur Seni Probo Wengker Studio has been implemented systematically and effectively in accordance with management principles, thereby supporting the optimal development of students’ artistic potential.